Impulse Buying Cosmetic Products: The Effect of Live Streaming Quality and Flash Sale - Insani, Nadhifah Qolbi; Awalil Fakhri, Erie (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The rapid increase in sales figures for the cosmetics industry in Indonesia over the last five years, which has even rivaled food and beverage sales figures, has made the cosmetics industry established as king in the FMCG line. Supported by the increasing phenomenon of online shopping, e-commerce platforms see this as an opportunity to attract potential consumers. One such platform is Shopee, which has enhanced its marketing strategy by presenting live streaming features and flash sale promotions. The interaction created between the live streamer and the audience, combined with the flash sale promotion, prompts potential consumers, who previously had no plans to buy, to make spontaneous purchases. This is commonly referred to as impulse buying. This research aims to measure the influence of live streamer quality and flash sales on impulse buying of cosmetic products on Shopee's live streaming. This research is a quantitative explanatory type with a replicative nature using the SEM-PLS analysis method. Data collection was conducted purposively on 180 respondents by distributing questionnaires. The results of this research indicate that live streamer quality has a significant effect on impulse buying, whereas flash sales do not have a significant effect on impulse buying.